Aluminum-based cladding coating and modification method thereof

By introducing components such as NiAl, Al, NH4Cl and Pt into the aluminum-based cladding coating and adopting laser cladding technology, the problems of reduced oxidation resistance and film peeling in high temperature, long-term and low-stress environments are solved, and significantly improved oxidation resistance and production efficiency are achieved.

CN119859784APending Publication Date: 2025-04-22XIAN THERMAL POWER RES INST CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510197720.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing high-temperature coating technology is difficult to effectively solve problems such as reduced oxidation resistance and film peeling in large-length-to-diameter structures, high-temperature, long-term and low-stress service environments of energy equipment flow components.

Method used

By using the modification method of aluminum-based cladding coating, by introducing components such as NiAl, Al, NH4Cl and Pt into the solid phase powder, a non-corrosive PtAl2-NiAl biphasic structure is formed, and the coating is prepared by using a laser cladding process to enhance oxidation and corrosion resistance.

Benefits of technology

It significantly improves the oxidation resistance and peeling resistance of aluminum-based cladding coatings, and the oxidation resistance is increased by 19-78 times in high-temperature water vapor environments, and is suitable for large aspect ratios and complex shape workpieces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859784A_ABST
    Figure CN119859784A_ABST
Patent Text Reader

Abstract

The modification method comprises the steps that after the surface of a workpiece to be plated is cleaned and preheated, cladding slurry is evenly sprayed to the surface of the workpiece, then natural air drying and medium-temperature curing are conducted, and finally the aluminum-based cladding coating is obtained through laser cladding; wherein the solid-phase cladding powder is prepared from the following components in percentage by mass: 60 to 80 percent of NiAl, 15 to 30 percent of Al, 2 to 7 percent of NH4Cl and 2 to 7 percent of Pt. According to the aluminum-based cladding coating and the modification method thereof, a prepared infiltrated layer is uniform in organization structure, moderate in thickness, sufficient in Al atom diffusion, good in metallurgical bonding with a base body, not prone to falling off and suitable for austenitic steel and high-temperature alloy parts used for workpieces with the large length-diameter ratio and various complex shapes such as large boilers and oil and gas field conveying pipelines; and the method has excellent industrial batch production benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material surface alloying and coating preparation, and specifically relates to an aluminum-based cladding coating and a modification method thereof. Background Art

[0002] Studies have shown that high-temperature coatings are effective in solving the problems of component oxidation corrosion, wear, and high-temperature ablation. However, existing high-temperature coating technologies are mostly used for hot-end components such as aircraft engine blades, rotors, and turbine disks that have high temperatures, short action times, and small sizes. Existing coating technologies are no longer applicable to the large aspect ratio structural characteristics, high temperature, long duration, and low stress service environment of energy equipment flow components. Currently, the Xi'an Thermal Engineering Institute has developed a high-temperature anti-oxidation coating preparation technology that is suitable for the large aspect ratio structural characteristics, high temperature, long duration, and low stress service environment of energy equipment flow components. The technology is mainly based on aluminide coatings. In actual unit operation tests, aluminide coatings also exhibit excellent anti-oxidation service performance. However, with the extension of service time, the increase of unit power and the complexity of the service environment, a single aluminide coating will inevitably face the phenomenon of decreased oxidation resistance and film peeling. In addition, after long-term service, the Al content of the film decreases, and the density and uniformity of the oxide film will also be lost, reducing the oxidation resistance of the coating. Therefore, it is necessary to develop a new type of anti-oxidation coating preparation technology and process with excellent oxidation resistance and anti-stripping ability, suitable for various complex-shaped workpieces with large aspect ratios. Summary of the invention

[0003] The embodiments of the present invention aim to solve at least one of the technical problems existing in the prior art, and provide an aluminum-based cladding coating and a modification method thereof, which is suitable for the preparation of anti-oxidation coatings on austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and other workpieces with large aspect ratios and various complex shapes.

[0004] To achieve the above object, the technical solution adopted by the present invention is a method for modifying an aluminum-based cladding coating, comprising the following steps:

[0005] Step 1, weigh and prepare solid phase cladding powder and liquid phase binder according to proportion, and prepare cladding slurry after stirring and ball milling for use;

[0006] Step 2: Clean and preheat the surface of the workpiece to be plated, and then spray the cladding slurry evenly onto the surface of the workpiece to be plated. After spraying, dry and solidify the workpiece;

[0007] Step 3: Place the workpiece after the spray coating is solidified in an inert atmosphere for laser cladding, obtain an aluminum-based cladding coating after cooling, and perform cladding residue treatment.

[0008] In some embodiments of the present invention, in step 1, the infiltration source includes NiAl and Al, the activator includes NH4Cl, the modifier includes Pt, and the binder includes ethyl acetate, wherein NiAl, Al, and Pt powders are all sieved through a 1000-mesh sieve.

[0009] In some embodiments of the present invention, the preparation method of solid phase cladding powder is as follows: solid phase components are weighed according to mass percentage, including 60-80% NiAl, 15-30% Al, 2-7% NH4Cl and 2-7% Pt, and the total mass of the solid phase components is maintained at 100%. After weighing, they are mixed by ball milling in a planetary ball mill, and the ball milling speed is 350-400rpm and the time is 12-24h.

[0010] In some embodiments of the present invention, the cladding slurry preparation method is as follows: the binder ethyl acetate is added to the uniformly mixed solid phase powder at a mass ratio of 10-30% of the solid phase component, and after being fully stirred for 2-4 hours, it is placed in a planetary ball mill for ball milling mixing, and the ball milling speed is 350-400rpm and the time is 8-12 hours.

[0011] In some embodiments of the present invention, in step 2, the workpiece surface is pretreated by cleaning with a high-pressure water gun and rinsing with alcohol or acetone; the preheating treatment is medium frequency preheating at 200-250°C for 30-60 minutes.

[0012] In some embodiments of the present invention, in step 2, the thickness of the preset spray layer is 1-5 mm, and the coating coverage is not less than 98%.

[0013] In some embodiments of the present invention, in step 2, the coating is dried by natural air drying for 24-48 hours, and the curing treatment is cured at 300-450° C. for 24-48 hours.

[0014] In some embodiments of the present invention, in step 3, the laser power is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 0-5r / min, and the Ar gas flow rate is 15-20L / min; the residue is treated by flushing with a high-pressure water gun or high-pressure air flow, and naturally dried.

[0015] The present invention also proposes an aluminum-based cladding coating, which is prepared according to the modification method of the aluminum-based cladding coating described in any of the above embodiments. The aluminum-based cladding coating has solid phase components weighed by mass percentage, including 60-80% NiAl, 15-30% Al, 2-7% NH4Cl and 2-7% Pt.

[0016] Compared with the prior art, the modification method of the aluminum-based cladding coating of the present invention also has at least the following beneficial effects:

[0017] 1. The present invention adds halide NH4Cl to the slurry components, which has the effect of promoting infiltration and activation, thereby improving the infiltration rate and the quality of the aluminum-based cladding coating;

[0018] 2. The present invention can form a PtAl2-NiAl dual-phase structure that is not easy to corrode by introducing the modified element Pt into the solid phase powder, thereby enhancing the oxidation and corrosion resistance of the aluminum-based cladding coating;

[0019] 3. The present invention prepares aluminum-based cladding coatings through a laser cladding process, which has concentrated heat, short action time, small thermal impact in the cladding zone, and high bonding strength between the coating and the base material;

[0020] 4. The present invention prepares aluminum-based cladding coatings through an integrated laser cladding process production line. The aluminum-based cladding coatings have high production efficiency, controllable thickness, high process repeatability, and are extremely practical and universal.

[0021] Furthermore, the introduction of Pt element modification can provide a channel for Al element to form a dense oxide, inhibit or reduce the external diffusion of alloy elements, accelerate the transformation of θ-Al2O3 to α-Al2O3, improve the film-base bonding strength, effectively inhibit internal oxidation and internal sulfidation, and enhance the oxidation resistance of aluminum-based cladding coatings.

[0022] Furthermore, the segmented slurry curing process of natural air drying combined with medium and low temperature curing effectively avoids the problem of micro cracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a cross-sectional morphology diagram of the aluminum-based cladding coating in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with relevant specific implementation methods.

[0025] The present invention provides a method for modifying an aluminum-based cladding coating, comprising the following steps:

[0026] Step 1, weigh the solid phase components according to the mass ratio, including 60-80% NiAl, 15-30% Al, 2-7% NH4Cl and 2-7% Pt, specifically, NiAl and AL are infiltration sources, NH4Cl is an activator, and Pt is a modifier, wherein NiAl, Al, and Pt powders are all sieved through a 1000-mesh sieve to keep the total percentage of all solid phase components at 100%; the weighed solid phase components are placed in a planetary ball mill at 350-400rpm for 12-24h to obtain a uniformly mixed powder, which is a solid phase cladding powder; then, ethyl acetate is added at a ratio of 10-30% of the mass of the solid phase components, wherein ethyl acetate is a binder, and after being fully mixed and stirred for 2-4h, it is placed in a planetary ball mill at 350-400rpm for 8-12h, and after completion, a uniformly mixed slurry is obtained, which is a cladding slurry.

[0027] Step 2, take out the workpiece to be plated, use a high-pressure water gun to clean the surface for 5-10 minutes to remove oil stains, dust, etc. on the workpiece surface and remove the oxide skin, and rinse it with alcohol or acetone to provide a neat and metallic surface for subsequent slurry spraying; then, preheat the workpiece at 200-250℃ for 30-60 minutes, spray the slurry to a suitable thickness at one time, and do not spray it in layers multiple times. Keep the spray layer thickness at 1-5mm and the coating coverage rate at least 98%. If the slurry layer is too thin, it will not provide sufficient penetration source, and if it is too thick, it will easily crack and peel off, affecting the uniformity of the penetration layer thickness; after spraying, let the workpiece air dry naturally for 24-48 hours, and then cure it at 300-450℃ for 24-48 hours. The segmented slurry curing process of natural air drying combined with medium and low temperature curing effectively avoids the problem of microcracks and tiny holes in the spray layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface.

[0028] Step 3: The laser cladding process is as follows: laser power is 2-2.8KW, scanning rate is 20-40mm / s, spot diameter is 3-5mm, workpiece rotation speed is 0-5r / min, Ar gas flow rate is 15-20L / min; after completion, cool to room temperature and flush the surface residue of the workpiece with a high-pressure water gun or high-pressure air flow.

[0029] Through the above-mentioned processes and steps, a modification method of an aluminum-based cladding coating of the present invention prepares an aluminum-based cladding coating with a thickness of 0.85-1.68 mm and good metallurgical bonding under the conditions of adjusting main process parameters such as solid phase component content, modifier addition content, spray layer thickness and laser cladding parameters; the aluminum-based cladding coating obtained by the present invention has an oxidation resistance that is 19-65 times higher than that of the parent material in a 600°C pure water vapor environment and 20-78 times higher than that of the parent material in a 650°C pure water vapor environment, which can be explained that the aluminum-based cladding coating prepared by the method of the present invention effectively improves the oxidation resistance of the alloy parent material in a water vapor environment.

[0030] The present invention also proposes an aluminum-based cladding coating, which is prepared according to the modification method of the aluminum-based cladding coating described in any of the above embodiments. The aluminum-based cladding coating has solid phase components weighed by mass percentage, including 60-80% NiAl, 15-30% Al, 2-7% NH4Cl and 2-7% Pt.

[0031] Example 1

[0032] Step 1. Weigh the solid phase components according to the mass ratio, including 60% NiAl, 30% Al, 5% NH4Cl and 5% Pt, place it in a planetary ball mill at 400 rpm for 12 hours to obtain a solid phase cladding powder; then, add 10% ethyl acetate and stir it for 4 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0033] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes, and use spraying to pre-set the slurry layer thickness to 3mm, keeping the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours, and cure it at 450°C for 48 hours.

[0034] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 40mm / s, a spot diameter of 5mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 20L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0035] The processes of Examples 2 to 9 are the same as those of Example 1. Examples 1 to 9 maintain the same solid phase components and liquid phase binder ratio. The specific laser cladding process conditions are detailed in Table 1. Table 1 is the specific parameters of Examples 1 to 9 of the method for improving the corrosion resistance of laser cladding aluminide coatings. According to the preparation steps in the above Example 1 and the specific preparation parameters in the table, aluminum-based cladding coatings with different thicknesses and Al atomic contents can be obtained.

[0036] Table 1

[0037]

[0038] By analyzing and studying the above examples, the thickness of the infiltration layer is measured to be about 0.85-1.68 mm. The specific results are shown in Table 1. The cross-sectional morphology of the infiltration layer is as follows: Figure 1 As shown in Table 1 and the cross-sectional morphology, it is found that the diffusion layer has a uniform structure, moderate thickness, sufficient diffusion of Al atoms, and a good metallurgical bond between the diffusion layer and the matrix, and is not easy to fall off.

[0039] Example 10

[0040] Step 1. Weigh the solid phase components according to the mass ratio, including 80% NiAl, 15% Al, 2% NH4Cl and 3% Pt, place it in a planetary ball mill at 350rpm for 24h to obtain a solid phase cladding powder; then, add 30% ethyl acetate and stir it for 2h, then place it in a planetary ball mill at 400rpm for 12h, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0041] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 24 hours and cure it at 300°C for 48 hours.

[0042] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.5KW, a scanning rate of 20mm / s, a spot diameter of 2mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0043] Embodiment 11

[0044] Step 1. Weigh the solid phase components according to the mass ratio, including 70% NiAl, 20% Al, 4% NH4Cl and 6% Pt, place it in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase cladding powder; then, add 20% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 350 rpm for 8 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0045] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 30 minutes, and use spraying to pre-set the slurry layer thickness to 2mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 24 hours and cure it at 450°C for 48 hours.

[0046] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 3mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 15L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0047] Example 12

[0048] Step 1. Weigh the solid phase components according to the mass ratio, including 70% NiAl, 21% Al, 2% NH4Cl and 7% Pt, place it in a planetary ball mill at 400 rpm for 12 hours to obtain a solid phase cladding powder; then, add 20% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 350 rpm for 12 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0049] Step 2: Clean the surface of the workpiece with a high-pressure water gun for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 24 hours and cure it at 400°C for 48 hours.

[0050] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 20mm / s, a spot diameter of 3mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0051] Embodiment 13

[0052] Step 1. Weigh the solid phase components according to the mass ratio, including 75% NiAl, 16% Al, 7% NH4Cl and 2% Pt, place it in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase cladding powder; then, add 30% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0053] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 24 hours and cure it at 450°C for 48 hours.

[0054] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 30mm / s, a spot diameter of 5mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 18L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0055] Embodiment 14

[0056] Step 1. Weigh the solid phase components according to the mass ratio, including 65% NiAl, 25% Al, 3% NH4Cl and 7% Pt, place it in a planetary ball mill at 350rpm for 12h to obtain solid phase cladding powder; then, add 30% ethyl acetate and stir it for 4h, then place it in a planetary ball mill at 400rpm for 8h, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0057] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 4mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 36 hours and cure it at 450°C for 48 hours.

[0058] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 5mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 20L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0059] Embodiment 15

[0060] Step 1. Weigh the solid phase components according to the mass ratio, including 72% NiAl, 20% Al, 5% NH4Cl and 3% Pt, place it in a planetary ball mill at 350rpm for 24h to obtain a solid phase cladding powder; then, add 20% ethyl acetate and stir it for 4h, then place it in a planetary ball mill at 400rpm for 8h, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0061] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece naturally for 48 hours, and cure it at 450°C for 48 hours.

[0062] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 4mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 15L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0063] Example 16

[0064] Step 1. Weigh the solid phase components according to the mass ratio, including 69% NiAl, 25% Al, 3% NH4Cl and 3% Pt, place it in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase cladding powder; then, add 30% ethyl acetate and stir it for 4 hours, then place it in a planetary ball mill at 400 rpm for 8 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0065] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece naturally for 24 hours, and cure it at 450°C for 48 hours.

[0066] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 35mm / s, a spot diameter of 4mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 18L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0067] The modification method of the aluminum-based cladding coating in the present invention is suitable for austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and other workpieces with large aspect ratios and various complex shapes. It has strong practicality, high permeation rate, excellent membrane-base bonding strength, and extremely good industrial mass production benefits.

[0068] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for modifying an aluminum-based cladding coating, characterized in that: The following steps are involved: Step 1, weigh and prepare solid phase cladding powder and liquid phase binder according to proportion, and prepare cladding slurry after stirring and ball milling for use; Step 2: Clean and preheat the surface of the workpiece to be plated, and then spray the cladding slurry evenly onto the surface of the workpiece to be plated. After spraying, dry and solidify the workpiece; Step 3: Place the workpiece after the spray coating is solidified in an inert atmosphere for laser cladding, obtain an aluminum-based cladding coating after cooling, and perform cladding residue treatment.

2. The modification method of an aluminum-based cladding coating according to claim 1, characterized in that: In step 1, the infiltration source includes NiAl and Al, the activator includes NH4Cl, the modifier includes Pt, and the binder includes ethyl acetate; wherein NiAl, Al, and Pt powders are all sieved through a 1000-mesh sieve.

3. The modification method of an aluminum-based cladding coating according to claim 1, characterized in that: In step 1, the solid phase cladding powder is prepared as follows: solid phase components are weighed according to mass percentage, including 60-80% NiAl, 15-30% Al, 2-7% NH4Cl and 2-7% Pt, and the total mass of the solid phase components is maintained at 100%. After weighing, they are mixed by ball milling in a planetary ball mill at a ball milling speed of 350-400rpm and a time of 12-24h.

4. The modification method of an aluminum-based cladding coating according to claim 1, characterized in that: In step 1, the cladding slurry preparation method is as follows: the binder ethyl acetate is added to the uniformly mixed solid phase powder at a mass ratio of 10-30% of the solid phase component, and after being fully stirred for 2-4 hours, it is placed in a planetary ball mill for ball milling mixing, and the ball milling speed is 350-400rpm and the time is 8-12 hours.

5. The modification method of an aluminum-based cladding coating according to claim 1, characterized in that: In step 2, the preheating treatment is medium frequency preheating at 200-250°C for 30-60 minutes.

6. The modification method of an aluminum-based cladding coating according to claim 1, characterized in that: In step 2, the prefabricated slurry layer has a thickness of 1-5 mm and a coating coverage of not less than 98%.

7. The modification method of an aluminum-based cladding coating according to claim 1, characterized in that: In step 2, the pre-coating is dried by natural air drying for 24-48 hours, and cured at 300-450° C. for 24-48 hours.

8. The modification method of an aluminum-based cladding coating according to claim 1, characterized in that: In step 3, the laser power is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 0-5r / min, and the Ar gas flow rate is 15-20L / min.

9. A coating suitable for aluminum-based cladding, characterized in that: The aluminum-based cladding coating is prepared according to the modification method of the aluminum-based cladding coating according to any one of claims 1 to 8, and the aluminum-based cladding coating comprises solid phase components weighed by mass percentage, including 60-80% NiAl, 15-30% Al, 2-7% NH4Cl and 2-7% Pt.

Citation Information

Patent Citations

  • Method for improving corrosion resistance of aluminide cladding coating

    CN118726971A

  • Rare earth element modified aluminide cladding coating and preparation method thereof

    CN118756132A

  • Modification method for improving oxidation resistance of aluminide cladding coating

    CN118773601A